2022
DOI: 10.1093/heapro/daac016
|View full text |Cite
|
Sign up to set email alerts
|

Participatory research in health promotion: a critical review and illustration of rationales

Abstract: In health promotion research, enthusiasm for patient and public involvement (PPI) is growing. However, a lack of conceptual clarity leads to ambiguities in participatory processes and purposes, and hampers efforts to achieve and evaluate PPI in research. This study provides an overview of its underlying reasons—or rationales—so as to better understand, guide and interpret PPI in research practice. We conducted a critical review to identify typologies of rationales for PPI. We re-categorized the different types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Often researchers reported that this was due to the systematic barriers described above, intensified when attempting to include carers from marginalized groups. Wider institutional understanding and support is required to provide the financial resources and opportunities that communicate to carers the value of their contributions 90,165 and fulfil the emancipatory potential of participatory research 163,166 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Often researchers reported that this was due to the systematic barriers described above, intensified when attempting to include carers from marginalized groups. Wider institutional understanding and support is required to provide the financial resources and opportunities that communicate to carers the value of their contributions 90,165 and fulfil the emancipatory potential of participatory research 163,166 …”
Section: Discussionmentioning
confidence: 99%
“…Wider institutional understanding and support is required to provide the financial resources and opportunities that communicate to carers the value of their contributions 90,165 and fulfil the emancipatory potential of participatory research. 163,166 This review found diverse and inconsistent descriptions of carer involvement, and a lack of clarity around terminology persists. 157 This search found studies claiming to use participatory methods where carers had only piloted materials or participated in interviews, corroborating worries that terms such as coproduction are being misused and diluted.…”
Section: Discussionmentioning
confidence: 99%
“…The principles of PAR include that community members are actively participating in every phase of the process, that is, researchers and community members are in mutually respectful partnership, bringing different strengths to the table. 25 The community members have situated knowledge and lived experience that is critical to a comprehensive understanding of the situation. [26][27][28] The principles of PAR include "a cooperative, iterative process of research and action in which non-professional community members are trained as researchers and change agents, and power over decisions are shared among the partners in the collaboration."…”
Section: Youth-led Participatory Action Researchmentioning
confidence: 99%
“…The principles of PAR include that community members are actively participating in every phase of the process, that is, researchers and community members are in mutually respectful partnership, bringing different strengths to the table 25 . The community members have situated knowledge and lived experience that is critical to a comprehensive understanding of the situation 26–28 …”
Section: Youth‐led Participatory Action Researchmentioning
confidence: 99%
“…While the participation ladder originates from the late sixties of the last century, the enthusiasm for patient and public involvement (PPI) in health research is growing more recently. In a critical review (Harting et al, 2022), five rationales for PPI are identified: (1) the democratic rationale reflects the normative right of citizens to have a voice in research;…”
Section: Participatory Approachesmentioning
confidence: 99%